Where the deer and the antelope play : the pastoral observations of one ignorant American who loves to walk outside - Offerman, Nick, 1970- (Dutton, 2021)
With wit, heartwarming stories and a keen insight into new and exciting ways to see both the past and the future of the country, the actor, writer and woodworker takes a literary journey to America's frontier to celebrate the people and landscape that have made it great.